Optimasi Parameter 3D Printing Menggunakan Material PP Daur Ulang pada Spesimen ASTM 638 D 10 type 1 dengan Response Surface Method - Felix Krisna Aji Nugraha; Bertha Bintari Wahyujati (Jurnal Teknologi, 2022)
Recycling plastic waste is one way to minimize the negative impact on the environment. The use of additive manufacturing which speeds up the prototyping process and product design currently uses a 3D printer with ABS and PLA filament materials. Remaining filaments and unused parts/prototypes, or products that have been manufactured with actual materials will be discarded. This causes waste for the environment. The use of recycled filament for 3d printing machines is one way to deal with plastic waste, besides that the use of recycled filament is a way to reduce the cost of plastic filament. Recycled plastic filament is used for 3d printer machines with the Fused Deposition Modeling (FDM) type. In this method the plastic filament material is melted and then extruded according to the desired pattern. In this study the results of the prints were tested using the tensile test method. Parameters used, print temperature, layer height, print speed. Response data analysis uses the Response Surface Method (RSM) with the Box-Behnken type. The results of the tensile test data were analyzed using Analysis of Variance (ANOVA). Based on the results of the ASTM D638-10 type 1 tensile test analysis, the print temperature parameter is 2600C, the layer height is 0.12 mm and the maximum print speed is 50 mm/s.